New Small Molecule Agonists to the Thyrotropin Receptor - Latif, Rauf (Thyroid, 2015)
BACKGROUND: Novel small molecular ligands (SMLs) to the thyrotropin receptor (TSHR) have potential as improved molecular probes and as therapeutic agents for the treatment of thyroid dysfunction and thyroid cancer. METHODS: To identify novel SMLs to the TSHR, we developed a transcription-based luciferase-cAMP high-throughput screening system and we screened 48,224 compounds from a 100K library in duplicate. RESULTS: We obtained 62 hits using the cut-off criteria of the mean±three standard deviations above the baseline. Twenty molecules with the greatest activity were rescreened against the parent CHO-luciferase cell for nonspecific activation, and we selected two molecules (MS437 and MS438) with the highest potency for further study. These lead molecules demonstrated no detectible cross-reactivity with homologous receptors when tested against luteinizing hormone (LH)/human chorionic gonadotropin receptor and follicle stimulating hormone receptor–expressing cells. Molecule MS437 had a TSHR-stimulating potency with an EC(50) of 13×10(−8) M, and molecule MS438 had an EC(50) of 5.3×10(−8) M. The ability of these small molecule agonists to bind to the transmembrane domain of the receptor and initiate signal transduction was suggested by their activation of a chimeric receptor consisting of an LHR ectodomain and a TSHR transmembrane. Molecular modeling demonstrated that these molecules bound to residues S505 and E506 for MS438 and T501 for MS437 in the intrahelical region of transmembrane helix 3. We also examined the G protein activating ability of these molecules using CHO cells co-expressing TSHRs transfected with luciferase reporter vectors in order to measure G(sα), G(βγ), G(αq), and G(α12) activation quantitatively. The MS437 and MS438 molecules showed potent activation of G(sα), G(αq), and G(α12) similar to TSH, but neither the small molecule agonists nor TSH showed activation of the G(βγ) pathway. The small molecules MS437 and MS438 also showed upregulation of thyroglobulin (Tg), sodium iodine symporter (NIS), and TSHR gene expression. CONCLUSIONS: Pharmacokinetic analysis of MS437 and MS438 indicated their pharmacotherapeutic potential, and their intraperitoneal administration to normal female mice resulted in significantly increased serum thyroxine levels, which could be maintained by repeated treatments. These molecules can therefore serve as lead molecules for further development of powerful TSH agonists.